2010
DOI: 10.1021/es102482j
|View full text |Cite
|
Sign up to set email alerts
|

Novel Methanogenic Rotatable Bioelectrochemical System Operated with Polarity Inversion

Abstract: A novel membraneless bioelectrochemical system termed rotatable bioelectrochemical contactor (RBEC) was fabricated and evaluated for its ability to recover useful energy (here methane) from a low organic strength wastewater. We studied the operational characteristics of the RBEC by operating it as a three-electrode electrolysis cell. A stack of conductive disks (each subdivided into two half disks), similar to rotating biological contactors, were rotated with one-half disk immersed in the wastewater and the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 20 publications
4
36
0
2
Order By: Relevance
“…Sasaki [5,6,7] found that methane yield has been significantly improved when MEC is used for solid waste treatment. Cheng [8] established a novel methanogenic rotatable BES operated with polarity inversion and they found the methane production rate was directly proportional to the applied electrical energy. Chae [9] studied the inhibition of methanogens in a two-chambered MEC and the results showed that abrupt decrease in temperature and pH had no effects on methanogenesis and exposing the anode biofilm to air was also ineffective in inhibiting specific methanogens.…”
Section: Introductionmentioning
confidence: 99%
“…Sasaki [5,6,7] found that methane yield has been significantly improved when MEC is used for solid waste treatment. Cheng [8] established a novel methanogenic rotatable BES operated with polarity inversion and they found the methane production rate was directly proportional to the applied electrical energy. Chae [9] studied the inhibition of methanogens in a two-chambered MEC and the results showed that abrupt decrease in temperature and pH had no effects on methanogenesis and exposing the anode biofilm to air was also ineffective in inhibiting specific methanogens.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms that develop on electrodes in MFCs under oxic cathode conditions have been shown to sustain current generation when the functions of the electrodes are switched (the cathode, for example, becomes the anode) (7,8,35). This indicates that both exoelectrogenic and electrotrophic microorganisms can be maintained in the electrode biofilms when the cathode is switched from oxic to anoxic conditions.…”
mentioning
confidence: 99%
“…As shown in Eqs. (5)(6)(7), the pH in the anode chamber can be controlled at 7.0 with the synergistic reaction between the BPM and exoelectrogens throughout the experiments, resulting in the high performance of MEDCC. Our MEDCC has better performance in terms of current density and Columbic efficiency than other bioelectrochemical systems, such as MDC and MEDC [15,24].…”
Section: Discussionmentioning
confidence: 99%
“…Because the exoelectrogens can utilize many kinds of organics and release electrons in the neutral solution at room temperature, the BES is potentially useful in the electrosynthesis field [2]. Many products have been reported to be produced in the BES, such as hydrogen, hydrogen peroxide, methane, and others [3][4][5][6]. However, the application of BES is still limited mainly because of relatively low values of the above products.…”
Section: Introductionmentioning
confidence: 99%